Use of bi-layer tablet technology to formulate dual-release dosage form of extended-release Montelukast and immediate-release Bilastine - Rahman, M A; Hossain, M S; Moulee, M M; Islam, M S; Shathi, A S; Paul, A; Abdurrahim, M; Hossain, M H (Bangladesh Journal of Scientific and Industrial Research, 2024)
Bilayer tablets containing Montelukast sodium, a bronchodilator, and Bilastine, an antihistamine, were formulated and assessed for pharmaceutical parameters. Twelve immediate-release Bilastine formulations, seven controlled-release Montelukast sodium formulations, and fourteen bilayer formulations were prepared. Stability studies employing FTIR, TGA, and SEM validated compatibility with excipients. Bilastine granules demonstrated bulk and tapped densities ranging from 0.33 to 0.38 g/mL and 0.429 to 0.488 g/mL, respectively. Carr’s index, Hausner ratio, and angle of repose suggested favorable flowability. All tablets met the weight variation criteria (<7.5%); however, Montelukast (M1, M2) exhibited hardness levels below 5 kg/cm², and the bilayer tablets demonstrated variability in hardness. Bilastine disintegrated in less than 3 minutes, whereas Montelukast required 15 to 60 minutes for disintegration. In dissolution tests, the B1-B3 Bilastine formulations demonstrated the highest release after 60 minutes, while the M6-M7 Montelukast formulations released over 60% within 6 hours. Six bilayer formulations; B2+M6, B2+M7, B3+M3, B3+M6, B3+M6, and B3+M7 exhibited optimal release for both active pharmaceutical ingredients (APIs), indicating that Montelukast sodium and Bilastine can be effectively formulated into bilayer tablets with satisfactory release profiles. Bangladesh J. Sci. Ind. Res. 59(4), 231-248, 2024